PERMASALAHAN YANG BISA MENIMBULKAN KONFLIK - -, Ismoyowati (UNIVERSITAS SLAMET RIYADI, 2014)
Essentially, human being is as individual creature and as social creature therefore the life of human cannot quit of conflict. Conflict is enabled to be happened in family, school, society, company, and everywhere which is caused by human as individual creature who wants to keep up his or her own life. On the other hand human as social creature needs the personality of others which automatically are related to more than one person that has different character and personality. The thing enables the existence of the conflict which caused by emulation, different idea, misunderstanding so that all the things can generate the problem which causes conflict or contradiction. Keywords : Problems, Conflicts